The effect of posture at the time of administration on the central depressant effects of the new hypnotic zopiclone. - Channer, K S (1984)
Nine healthy volunteers swallowed 7.5 mg zopiclone in the standing and lying positions on different occasions. Plasma concentrations of zopiclone and psychometric tests, including simple and complex reaction time, and critical flicker fusion threshold, were performed at regular intervals after drug administration. The results show that when the drug was swallowed in the supine position, there was a significant delay in the onset of the impairment of psychomotor function, with prolongation in time to peak impairment by 30-40 min (P less than 0.02). The overall impairment in psychomotor performance was found to be significantly less after administration of the drug in the supine position (P less than 0.005). Pharmacokinetic analysis revealed a prolongation in lag time of greater than 20 min before absorption began (P less than 0.002) after supine drug administration, with a significantly lower rate constant of absorption (P less than 0.02). Area under the plasma concentration-time curve extrapolated to infinity and rate constant of elimination were not significantly different between the two modes of administration. We conclude that to obtain a rapid and complete effect from the hypnotic zopiclone, the tablet should be swallowed in the standing position.